2020
DOI: 10.1007/s11596-020-2186-0
|View full text |Cite|
|
Sign up to set email alerts
|

Kinetic Characterization of Tyrosinase-catalyzed Oxidation of Four Polyphenols

Abstract: Phenolic compounds such as chlorogenic acid, cryptochlorogenic acid, neochlorogenic acid and caffeic acid are widely distributed in fruits, vegetables and traditional Chinese medicines with a wide range of biological activities. Tyrosinase plays a critical role in the food industry, but recent studies have proposed unexplored aspects of clinical application. Tyrosinase-catalyzed oxidation of four polyphenols as well as its underlying mechanism remains unclear. In the current work, we investigated the kinetic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Melanogenesis, the process of melanin production, plays a crucial role in skin pigmentation and can be implicated in various skin conditions [12]. Mushroom tyrosinase is a well-established enzyme used to test compounds that inhibit melanogenesis [51] and the results indicated that UMS significantly suppressed mushroom tyrosinase activity in a concentration-dependent manner, with a lower IC 50 value (48.60 ± 1.02 µg/mL) compared to the positive control, arbutin (IC 50 = 131.03 ± 2.01 µg/mL) (Figure S4).…”
Section: Depigmenting Effect Of Ums On Hyperpigmented Melanocyte (Mnt...mentioning
confidence: 99%
“…Melanogenesis, the process of melanin production, plays a crucial role in skin pigmentation and can be implicated in various skin conditions [12]. Mushroom tyrosinase is a well-established enzyme used to test compounds that inhibit melanogenesis [51] and the results indicated that UMS significantly suppressed mushroom tyrosinase activity in a concentration-dependent manner, with a lower IC 50 value (48.60 ± 1.02 µg/mL) compared to the positive control, arbutin (IC 50 = 131.03 ± 2.01 µg/mL) (Figure S4).…”
Section: Depigmenting Effect Of Ums On Hyperpigmented Melanocyte (Mnt...mentioning
confidence: 99%